Decision in implementation of production capacity planning determinated by usage of sensitive analysis - Tomáš Poláček; Martina Žákovská (Trends Economics and Management, 2018)
Purpose of article: Effective planning and management of material flow and production resources, i.e. production planning and control is generally regarded as crucial for the success of manufacturing companies. It involves managing all aspects of production, including materials management, planning and scheduling of machines and human resources and coordination of suppliers and key customers. They were followed a more advanced concept MRP II, controls all production resources. Despite production planning using ERP systems, based on MRP II logic. With this tool can company effectively balance all production resources and in the optimal way to schedule production orders according to production capacity. Implementation of capacity planning in the company introduces a number of problems associated with the requirements of quality information and accurate data on which is a production plan created. Decision on the implementation of capacity planning is a challenge associated with high risk and the need to consider the order of several months in advance uncertainty. At points where we do not have full control over decisions, it can be used heuristic methods of decision-making through a decision tree using the known probabilities, and with a partial ignorance of using interval arithmetic. Methodology/methods: Solving within decision tree with known probabilities obtained from expert in capacity planning. Scientific aim: Find the upper limit worth of implementation of capacity planning or MRP-II. Findings: The difference between the implementation the APS and MRP-II based on profits determinate by time. Conclusions: Enterprise should have after implementation of its own data to the model make decision of what kind of capacity planning is profitable for its purpose.
Keywords: O33; O21; D70; 650; Capacity planning; MRP II; Decision making; Interval arithmetic